ANALISIS MANFAAT KOPERASI, PENDAPATAN, DAN TINGKAT KESEJAHTERAAN ANGGOTA KOPERASI LEMBAGA KEUANGAN MIKRO AGRIBISNIS (LKM-A) GAPOKTAN SARI MAKMUR KECAMATAN METRO TIMUR KOTA METRO - Dewi Lestari Putri; Dyah Aring Hepiana Lestari; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This research aims to analyze the cooperative economic and noneconomic benefits received by members of LKM-A Gapoktan Sari Makmur Cooperative, the household income of cooperative members, and  welfare level of cooperative members.  This research  was conducted by case study method in LKM-A Gapoktan Sari Makmur Cooperative, East Metro subdistrict.  The locations were selected purposively.  Data was collected from January to February 2018.  The 42 research samples were taken by simple random sampling.  Data was analyzed by the economic benefits of cooperative analysis, analysis of noneconomic benefits using Customer Satisfaction Index and Importance Performance Analysis, the household income of cooperative members, and analysis of welfare level.  The results showed that the economic benefits received cooperative members was on low category and members were satisfied with the service of cooperative and fulfilled their needs.  The household income of cooperative members was on high category.  All of cooperative members considered as welfare families.Key word : benefits, cooperative, income, welfare